513. Viral kinetics of SARS-CoV-2 in patients with COVID-19. (31st December 2020) - Kim, Da Young; Lee, Ju-Hyung; Oh, Hyeon Jeong; Seo, Jun-won; Yun, Na Ra; Kim, Choon-Mee; Kim, Dong-Min
Abstract: Background: As only few studies have analyzed viral kinetics between the incubation and symptomatic periods of COVID-19 patients, we investigated the viral kinetics and compared viral loads between patients with mild and severe COVID-19. Methods: We determined the viral kinetics of 10 patients diagnosed with COVID-19 at Chosun University Hospital. Six patients were classified into the "mild" group and 4 into the "severe" group according to supplemental oxygen use during admission. Samples were collected via nasopharyngeal swabs and sputum specimens. SARS-CoV-2 was detected using real-time reverse transcription-polymerase chain reaction (RT-PCR). Chest radiograph scores during hospitalization were obtained Results: Ct values of the upper respiratory tract specimens were low during the early stages after symptom onset but gradually increased over time in both groups. The severe group had lower Ct values than the mild group. The Ct values of the RdRP and E genes on day 6 after symptom onset were significantly lower in the severe group than in the mild group (p < 0.05). Three of 6 patients had positive results on RT-PCR even before symptom onset; 2 of them had the lowest Ct values. The chest radiograph scores were higher in the severe group than in the mild group, and the score in the severe group was the highest at approximately 3 weeks after symptom onset. Ct values when the RdRP gene and E gene were targeted to detect SARS-CoV-2 on the basis of the days after symptom onset in all the patients Conclusion: Viral load and chest radiograph scores were significantly different between the severe and mild groups of COVID-19 patients. Disclosures: All Authors : No reported disclosures